1994
DOI: 10.1159/000261615
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization and Degradation of Demineralized Dentin Matrix in situ

Abstract: Lesion formation in dentin involves demineralization followed by degradation of the exposed organic matrix. Proteinases from microorganisms present in the dentin are believed to play an important role in the breakdown of the dentinal collagen. In this study, the microflora colonizing decalcified dentin matrix, placed in situ, was identified. The gelatinolytic activity of the isolated strains was assessed and related to the degradation of the dentin matrix. The predominant species found were Streptococcus mitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 17 publications
1
26
0
3
Order By: Relevance
“…Oral bacteria may release proteolytic enzymes that degrade the collagenous dentine matrix. In a study investigating the colonization and degradation of similar dentine specimens [Van Strijp et al, 1994], gelatinolytic strains were found in the predominant microflora. Although no correlation was found between the loss of collagen and the presence of these strains, the involvement of bacterial enzymes in the process of dentine degradation cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral bacteria may release proteolytic enzymes that degrade the collagenous dentine matrix. In a study investigating the colonization and degradation of similar dentine specimens [Van Strijp et al, 1994], gelatinolytic strains were found in the predominant microflora. Although no correlation was found between the loss of collagen and the presence of these strains, the involvement of bacterial enzymes in the process of dentine degradation cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In the past the role of bacterial enzymes has been investigated. Although bacterial strains that produce proteolytic enzymes were found in carious dentine, a direct action towards degradation of dentine collagen remained questionable [Van Strijp et al, 1994. However, bacterial products such as acids and proteinases could be indirectly involved in matrix degradation by activating host-derived proteinases [Uitto and Raeste, 1978;Sorsa et al, 1992].…”
mentioning
confidence: 99%
“…Once demineralisation of the dentine has been initiated other bacteria can migrate into the developing lesion. Generally, current treatments of caries attempt to remove all infected tissue but this cannot be guaranteed [van Strijp et al, 1994;Bjørndal et al, 1997]. However Kidd et al [1996] have proposed that the removal of only the softened and wet dentine is necessary, the effective sealing of the cavity with a restorative being suffi cient to achieve 'healing of the lesion' as the bacteria become quiescent.…”
mentioning
confidence: 99%
“…References has previously been studied by Armstrong [1958Armstrong [ , 1961, Goldberg and Keil [1989], van Strijp et al [1992van Strijp et al [ , 1994 and Tjäderhane et al [1998]. Although not directly comparable, these published results did not show a total degradation of carious dentin.…”
mentioning
confidence: 77%